Analisis Hasil Koding yang Dihasilkan oleh Coder di Rumah Sakit Pemerintah X di Kota Semarang Tahun 2012 - Yuniati, Dewi Indah (UI Scholars Hub, 2017)
Coders affect hospital revenue due to their ability to determine specific code using ICD for diagnoses and procedures stated in medical record. This study aimed to determine the competence of coder in X Hospital and potential losses that may occur. Quantitative method was used in this study, involving 6 coders who were divided into 2 groups: standard and test groups, based on years of experience and followed trainings. Coding results and the amount of the claim were compared between groups. The study showed coder‘s competence still needs to be improved. This was characterized by a high average under coding result that reached 32.6% and potentially lowering hospital revenue by an average of 4.2% of claims that should be obtained by the hospital.